Astaxanthin Is Able to Prevent Alcohol-Induced Dysfunction of Liver Mitochondria - Olga Krestinina; Irina Odinokova; Linda Sotnikova; Roman Krestinin; Alena Zvyagina; Yulia Baburina (MDPI AG, 2022)
The search for new targets for the pathological action of ethanol remains an urgent task of biomedicine. Since degenerative changes in the liver are associated with the development of oxidative stress, antioxidants are promising agents for the treatment of alcohol-related diseases. In this work, we studied the ability of the carotenoid antioxidant, astaxanthin (AX), to prevent ethanol-induced changes in the liver of rats. It was shown that AX is able to protect the structure of mitochondria from degenerative changes caused by ethanol to improve mitochondrial functions. AX positively influences the activity and expression of proteins of the mitochondrial respiratory chain complexes and ATPase. In addition, a protective effect of AX on the rate and activity of mitochondrial respiration was demonstrated in the work. Thus, studies have shown that AX is involved in protective mechanisms in response to ethanol-induced mitochondrial dysfunction.